Associations between Depression and Health Behaviour Change: Findings from 8 Cycles of the Canadian Community Health Survey. (January 2019) - Clayborne, Zahra M.; Colman, Ian
Objectives: The primary objective of this study was to examine associations between depression and several measures of health behaviour change across 8 cycles of a population-based, cross-sectional survey of Canadians. The secondary objective of this study was to describe the prevalence of the types of health behaviour changes undergone/sought and types of barriers to change reported, comparing those with and without depression. Methods: The sample comprised 65, 801 respondents to the Canadian Community Health Survey between 2007 and 2014. Past-year depression was assessed via structured interview (CIDI-SF). Measures of health behaviour change included recent changes made, desire to make changes, and barriers towards making changes. Analyses involved logistic regression, with estimates across cycles pooled using fixed-effects meta-analyses. Pooled prevalences of types of health behaviour changes undergone/sought and types of barriers to change experienced were reported, and associations with depression were examined. Results: Depression was associated with higher odds of reporting a recent health behaviour change (pooled odds ratio [OR] = 1.39; 95% confidence interval [CI], 1.30 to 1.48), desire to make health behaviour changes (pooled OR = 1.61; 95% CI, 1.49 to 1.74), and barriers towards change (pooled OR = 1.54; 95% CI, 1.44 to 1.65). The most common change undergone and sought was increased exercise; the most common barrier reported was a lack of willpower. Conclusions: Individuals dealing with depression are more likely to report recent health behaviour changes and the desire to make changes but are also more likely to report barriers towards change.